Facile Synthesis of Ultra‐Small Few‐Layer Nanostructured MoSe2 Embedded on N, P Co‐Doped Bio‐Carbon for High‐Performance Half/Full Sodium‐Ion and Potassium‐Ion Batteries. Issue 58 (17th September 2019) - Zeng, Lingxing; Kang, Biyu; Luo, Fenqiang; Fang, Yixing; Zheng, Cheng; Liu, Junbin; Liu, Renpin; Li, Xinye; Chen, Qinghua; Wei, Mingdeng; Qian, Qingrong
Abstract: Sodium/potassium‐ion batteries (SIBs/PIBs) arouse intensive interest on account of the natural abundance of sodium/potassium resources, the competitive cost and appropriate redox potential. Nevertheless, the huge challenge for SIBs/PIBs lies in the scarcity of an anode material with high capacity and stable structure, which are capable of accommodating large‐size ions during cycling. Furthermore, using sustainable natural biomass to fabricate electrodes for energy storage applications is a hot topic. Herein, an ultra‐small few‐layer nanostructured MoSe2 embedded on N, P co‐doped bio‐carbon is reported, which is synthesized by using chlorella as the adsorbent and precursor. As a consequence, the MoSe2 /NP‐C‐2 composite represents exceedingly impressive electrochemical performance for both sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs). It displays a promising reversible capacity (523 mAh g −1 at 100 mA g −1 after 100 cycles) and impressive long‐term cycling performance (192 mAh g −1 at 5 A g −1 even after 1000 cycles) in SIBs, which are some of the best properties of MoSe2 ‐based anode materials for SIBs to date. To further probe the great potential applications, full SIBs pairing the MoSe2 /NP‐C‐2 composite anode with a Na3 V2 (PO4 )3 cathode also exhibits a satisfactory capacity of 215 mAh g −1 at 500 mA g −1 after 100 cycles. Moreover, it also delivers a decent reversible capacity of 131 mAh g −1 at 1 A g −1 even after 250 cycles for PIBs. Abstract : Renewable battery precursor : MoSe2 ‐NP‐C‐2 was initially synthesized through a one‐step calcination strategy by using waste chlorella as a precursor and absorbent, fabricating few‐layer MoSe2 embedded tightly on bio‐carbon, which exhibited promising potential as an alternative material for sodium‐ion half/full batteries and potassium‐ion batteries (see scheme).